Preliminary palaeomagnetic results from medium grade metacarbonates of the Lesser Himalaya - Schill, E.; Appel, E.; Gautam, P.; Singh, V. K. (Journal of Nepal Geological Society, 1998)
First investigations of metacarbonates of the Lesser Himalaya close to the Main Central Thrust (MCT) demonstrate the suitability of medium grade metacarbonates for palaeomagnetic studies. Stable directions were obtained for a secondary thermoremanent magnetisation with unblocking spectra between 200- 350oC, indicating pyrrhotite as the remanence carrier. The occurrence of pyrrhotite is evidenced in several sites by rockmagnetic investigations. Significant mean directions were found in sampling sites located south of the Manaslu massif (central Nepal) and also in the Alaknanda valley (Garhwal Himalaya, India). More stable remanences in the Alkananda valley can be related to single domain (SD) pyrrhotite whereas higher instabilities in central Nepal might be due to smaller grain sizes around the SD superparamagnetic transition.